Indisputable reasons for reform of the United Nations - Mutagirov, Dzhamal Z. (Advances in Social Sciences Research Journal, 2018)
There are few people now who believe that there is an effectively functioning Center of joint solution of the problems of peace and security in the world. The United Nations, existing three quarters of a century, had not always coped with its mission properly. If the first four decades of its activity the UN really tried to function as a global Institute of peace and security, in the last three decades, negative in its activity have prevailed over positive. In many cases it looked helplessly at the violations of the international law by its members. Some States do no longer reckon with it. Why is this happening and how ought to change the situation? The article shoes the main causes the UN ineffectiveness and proposes some possible ways to its reforming. The Global Institute for peace and security may not be reformed by itself, and not by the ‘great powers’ only, but by democratically elected representatives of all the nations of the world at an international conference on a base of their true equality. The structure of the governing bodies and their authorities should be defined in accordance with, firstly, the theory of democracy, and secondly, the real challenges of humankind in the twenty-first century.